Impact of Retail Lending on Profitability of DCCBs of Punjab - Gautam, Vandana (Indian Journal of Finance, 2019)
The cooperative banks were mainly established in India with a view to providing economic support to farmers by making available to them hassle-free loans. However, as a consequence of financial sector reforms, these banks faced a firm competition from several quarters on the account of gushing technical expertise, prudential guidelines, custom-built central banking systems, and a deregulated and market focused banking system. Consequently, cooperative banking organizations gradually advanced and prepared themselves to efficaciously meet recent challenges by reconceiving their operational strategies. One such change which came in a big way was the diversification of their loan portfolios-the movement from agricultural intensive loaning to retail loaning. Although profit was considered a forbidden word for cooperative banks, yet in view of the above changes, it became imperative to measure the change in the profitability performance of the cooperative banks. This paper made an attempt to study the outcome of retail loaning on the functioning of District Central Cooperative Banks (DCCBs) of Punjab by using secondary data. The paper examined the profitability of selected DCCBs in Punjab by determining the differential yield rate which is the difference in weighted average rate of return on total loans and weighted average rate of return on retail loans and further also determined the differential earnings resulting due to retail lending. The study also pin pointed major lacunas in cooperative banking relating to retail lending policies and otherwise and gave suggestions for their improvement.